Understanding pain in women with polyendocrine metabolic ovarian syndrome: health risks and treatment effectiveness - Tess Cherlin; Stephanie Mohammed; Samantha Strydesky; Sasha Ottey; Katherine Sherif; Shefali Setia Verma (eLife, 2026)
Background: Polycystic ovary syndrome (PCOS), recently renamed as polyendocrine metabolic ovarian syndrome (PMOS), is a prevalent endocrine disorder in women, often accompanied by various symptoms, including significant pain, such as dysmenorrhea, abdominal, and pelvic pain, which remains underexplored. Methods: This retrospective study examines electronic health records (EHR) data to assess the prevalence of pain in women with PMOS. Conducted in January 2026, using data from 120 Health Care Organizations within the TriNetX Global Network, the study involved 103,675,738 women from diverse racial backgrounds. The analysis focused on the prevalence of pain among women with PMOS, both overall and in those prescribed PMOS-related medications. Relative risk ratios (RR) were calculated for future health outcomes and stratified by self-reported race. Results: The study found that 20.67% of women with PMOS experienced pain, with the highest prevalence among Black or African American (32.70%) and White (30.78%) populations. Both the PMOS and PMOS and Pain cohorts exhibited increased RR for various health conditions, with significant differences noted across racial groups for infertility, ovarian cysts, obesity, and respiratory diseases. Additionally, women with PMOS who were treated with PMOS-related medications showed a decrease in pain diagnoses following treatment. Conclusions: This study highlights the critical need to address pain in the diagnosis and management of PMOS due to its significant impact on patient health outcomes. Funding: Tess Cherlin was supported by NIH | National Institute of General Medical Sciences (NIGMS) (grant # K12GM081259 (HHS)).